A case of prostatic carcinoma with osteolytic bone metastases - Fukuoka, H (Hinyokika kiyo. Acta urologica Japonica, 1988)
A 55-year-old man consulted us on December 3, 1986 with the chief complaints of left leg pain, disturbance in gait and dysuria. On digital rectal examination his prostate was found enlarged to a hen's egg size and increased in consistency. He was admitted to the hospital under the suspicion of prostatic cancer on December 8, 1986. Scout kidney-ureter-bladder X-ray revealed extensive osteolytic lesions in the left iliac and pubic bones as well as in the sacrum. Needle biopsy of the prostate demonstrated moderately differentiated adenocarcinoma, leading to a diagnosis of prostatic cancer with osteolytic bone metastases. Bone scintigraphy showed increased radioactivity uptake by the left iliac and pubic bones. Pelvic CT disclosed large tumor masses in the left ilium and sacrum, which on bone biopsy were identified as poorly differentiated adenocarcinoma. Endocrine therapy with estramustinphosphate and castration was performed along with transurethral resection of prostate. At week 16 after initiating the therapeutic regimen the patient was entirely free from disturbance in gait and the tumor mass of the left iliac bone had disappeared almost completely on the computed tomogram at week 18, although osteolytic lesions still persisted on the x-ray. This case deserves special note because endocrine therapy markedly reduced the size of the bone tumors, in spite of osteolytic bone metastases of prostatic cancer with computed tomographic evidence of large metastatic tumor masses